Faktor-Faktor Yang Berhubungan Dengan Pernikahan Usia Dini Di Kecamatan Plaosan Kabupaten MagetanJawa Timur Tahun 2015 - Dwinanda, Aditya Risky; , Anisa Catur Wijayanti, SKM., M.Epid; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Early marriage has an impact on the health of young couples because it can affect the maternal mortality rate. The purpose of this study was to analyze the factors that influence early marriage age in the District Plaosan Magetan East Java. This type of research is observational research with case control design. The population in this study were women who were married in the District Plaosan Magetan East Java in 2014. The sample in the ratio 1: 1, with cases as much as 76 respondents and 76 control respondents. Techniques using the statistical test Chi Square and Fisher's Exact. The results showed that there was a correlation between respondents' education (p-value = 0.000), father's education (p-value = 0.000; OR = 7.52; 95% CI = 3.643 to 15.519), mother's education (p-value = 0.000; OR = 9.821; 95% CI = 4.657 to 20.714), family economic status (p-value = 0.000; OR = 47.143; 95% CI = 15.299 to 145.266), mother's occupation (p-value = 0.001; OR = 9.098; 95% CI = 2,002- 41.344), respondents knowledge (p-value = 0.000; OR = 4.286; 95% CI = 2.082 to 8.825) and there is no relationship between father's occupation with early marriage age (p-value = 1.00). Keywords : early marriage age, education, family economic status, occupation.